Laser-assisted gingivectomy in pediatric patients: A novel alternative treatment - G Gontiya; S Bhatnagar; U Mohandas; S R Galgali (Wolters Kluwer Medknow Publications, 2011)
Gingival enlargement is quite a common pathology in pediatric patients and may be inflammatory, noninflammatory, or a combination of both. Idiopathic gingival fibromatosis, although rare, is a slowly progressive benign enlargement that affects the marginal gingiva, attached gingival, and interdental papilla. The fibromatosis may potentially cover the exposed tooth surfaces, causing esthetic and functional problems. The treatment of gingival fibromatosis is essential because it causes difficulties with mastication, speech problems, mispositioning of teeth, esthetic effects, and psychological difficulties for the patient. Traditional gingivectomy procedures have been a challenge for dentists who confront issues of patient cooperation and discomfort. In the last decade, laser procedures in oral cavity had shown many optimum effects in both hard and soft tissue procedures. Laser soft-tissue surgery has been shown to be well accepted by children. The following case report describes a laser-assisted gingivectomy procedure performed on a 13-year-old female.